ANALISIS DAMPAK PELAKSANAAN PROGRAM MBKM TERHADAP IKU PERGURUAN TINGGI PADA MAHASISWA PGSD UNIVERSITAS BUNG HATTA DALAM MENGHASILKAN LULUSAN YANG TANGGUH BERSAING DI ERA GLOBAL - Risa Yulisna; Rieke Alyusfitri; Ira Rahmayuni Jusar (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia launched the Independent Learning Campus Merdeka Program (MKBKM) which is one of the breakthroughs in the era of digitalization in the field of education. This MBKM program provides opportunities for student exchange and also opens the boundaries of the (physical) classroom into a digital space. This study aims to analyze the implementation of the MBKM program in the Bung Hatta University Elementary School Teacher Education Study Program. In addition, this study aims to analyze the various obstacles faced during the implementation of the MBKM program. The MBKM policy is intended to fulfill the study period and load for undergraduate or applied undergraduate students by following the entire learning process in the PGSD study program at Bung Hatta University according to the period and study load. Students can also follow the learning process to fulfill part of the time and outside the study program.